Environmental Indicators and Hotel Restaurants Performance - Juliana Langgat (European Publisher, 2020)
The need of tourism and hospitality businesses to be more environmentally friendly has led the hotels industry to open their doors to sustainable practices. Thus, the need to implement sustainability initiatives and other programme has led to hotels in Malaysia in adopting this practices to deliver quality services. The hotel restaurant business has embarked into this sustainable practice to increase hotel restaurant profitability and performance. This study is aim to investigate the environmental indicators that could influence hotel restaurant performance in Malaysia. There are 169 hotels has participated in this quantitative approach study. In order to conduct this study, a self-administrative questionnaire was used to investigate the issue. Chi-square analysis was performed to determine whether environmental indicators influence hotel restaurant performance. The findings of this study have confirmed, introduced environmental indicators in a restaurant operations could improve hotel restaurant performance by enhancing the hotel image, improve relationships with the local community and give a promotion advantage over competitors. It also grow the profitability, and enhance customer and employee satisfaction. The discussion highlights the need for the Malaysian hotel industry to move towards sustainable business operations.